3D printing of customized functional devices for smart biomedical systems - Hao Yang; Haiqiu Fang; Chongze Wang; Yanjiao Wang; Chao Qi; Yunlong Zhang; Qiang Zhou; Mengxin Huang; Min Wang; Mingbo Wu (SmartMat, 2024)
Abstract The escalating demands for smart biomedical systems ignite a significantly growing influence of three‐dimensional (3D) printing technology. Recognized as a revolutionary and potent fabrication tool, 3D printing possesses unparalleled capabilities for generating customized functional devices boasting intricate and meticulously controlled architectures while enabling the integration of multiple functional materials. These distinctive advantages arouse a growing inclination toward customization and miniaturization, thereby facilitating the development of cutting‐edge biomedical systems. In this comprehensive review, the prevalent 3D printing technologies employed in biomedical applications are presented. Moreover, focused attention is paid to the latest advancements in harnessing 3D printing to fabricate smart biomedical systems, with specific emphasis on exemplary ongoing research encompassing biomedical examination systems, biomedical treatment systems, as well as veterinary medicine. In addition to illuminating the promising potential inherent in 3D printing for this rapidly evolving field, the prevailing challenges impeding its further progression are also discussed. By shedding light on recent achievements and persisting obstacles, this review aims to inspire future breakthroughs in the realm of smart biomedical systems.